Eco-friendly corrosion inhibitor chitosan methionine for carbon steel in 1 M hydrochloric acid solution: experimental and theoretical approach - S. F. Hamza; Seham Shahen; Amal M. Abdel‑karim; Ahmed A. El-Rashedy; Amira M. Hyba (Scientific Reports)
Abstract There is a high demand for high performance, effective and eco-friendly corrosion inhibitors for industrial applications. Consequently, many researchers are focused on developing efficient, cost-effective materials to protect metals. In this study, an ecofriendly chitosan methionine derivative (M) was developed, synthesized, characterized, and tested for its anticorrosion properties. The ability of this compound as a corrosion inhibitor for carbon steel (CS) was confirmed through weight loss measurements (WL), potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS) studies in a 1.0 M hydrochloric acid solution. The findings showed that the inhibitor, M, achieved a maximum inhibition efficiency of 99.8% at a concentration of 100 ppm by the PDP method. Additionally, the corrosion potential value, being less than 85 mV, supported classifying M as a mixed-type inhibitor with a cathodic tendency. The adsorption behavior of the inhibitor on the CS surface was consistent with Langmuir’s adsorption isotherm. EIS data also confirmed that increasing inhibitor concentration raised the charge transfer resistance (R ct), indicating improved protection. Surface examination using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) revealed the formation of a protective layer of the M molecules on the CS surface. Moreover, theoretical studies, including analyses of the highest occupied molecular orbital (EHOMO), lowest unoccupied molecular orbital (ELUMO), dipole moment (µ), were thoroughly examined. Overall, both experimental and theoretical findings demonstrate that this derivative can effectively form a protective layer and mitigate corrosion.